Analysis of combustion characteristics, engine performances and exhaust emissions of long-chain alcohol-diesel fuel blends - Hazrulzurina, Suhaimi (2019)
In the present life, petroleum-based fuels have been one of the most in demand energy source for various purposes and application. Due to this, problems such as higher gas emissions from petroleum-based fuels have forced many governments to introduce stringent regulations and concerns over energy security. Previously, the short-chain alcohol such as methanol, ethanol and propanol had been used as an oxygenated element to increase oxygen content in diesel fuels. However, short-chain alcohol-diesel blends have disadvantages such as low cetane number, low calorific value as well as increase of NOx and low miscibility with diesel fuel (DF). Due to the problems with the used of shortchain alcohol, many researchers have shown interest on long-chain alcohol such as pentanol and hexanol. This is due to the thermophysical properties of long-chain alcohol which are much better than short-chain alcohol in terms of density, kinematic viscosity, cetane number, low calorific value and miscibility. In relation to this, long-chain alcohols, 1-pentanol (1-PN) and 2-ethyl 1-hexanol (2-EH) are blended with DF to produce longchain alcohol-diesel fuel blends. Thus, the first objective of this study was to analyze new formulation of 1-pentanol-diesel fuel blends and 2-ethyl 1-hexanol-diesel fuel blends by study their thermophysical properties. Besides that, it was necessary to investigate the effect of 1-pentanol-diesel fuel blends and 2-ethyl 1-hexanol-diesel fuels on combustion characteristic, performance and emissions in diesel engine. Last objective was to determine the correlation between the blend ratio and engine performance within research scope. In order to obtain objectives, 5%, 10% and 20% of 1-PN and 2-EH are added into DF to produce long-chain alcohol-diesel fuel blends. The fuel blends were prepared by using Hielscher UP400S ultrasonic emulsifier machine at stirring speed 40% Hz and amplitude 0.5%. The discussion will focus on combustion characteristics, engine performance and exhaust emissions of single cylinder diesel engine YANMAR TF120M at constant engine speed of 1800rpm under various engine loads (0%, 25%, 50%, 75%, and 100%). The complete results for thermophysical properties test and engine test obtained for DF, PE5, PE10, PE20, HE5, HE10 and HE20. The density, cetane number, calorific value and viscosity of fuel blends decrease compared to DF. Performance analysis showed that BTE had increased by 7.03%, 12.09%, 17.55%, 12.25%, 12.95%, and 19.67% for PE5, PE10, PE20, HE5, HE10 and HE20 than that DF. The BSFC for fuel blends also decreased 8.51% for PE5, 10.16% for PE10, 12.08% for PE20, 8.93% for HE5, 10.87% for HE10 and 10.99% for HE20. The EGT for all fuels blends are lower except for PE5 which had increase of EGT due to increase of O2 contains. Furthermore, results have reported that fuel blends had higher CO and EGO. But, lower CO2 and NOx emissions found in fuel blends compared to DF. Additionally, the HC was higher for all fuel blends than DF except for HE5 with reduced of HC emission. Based on the results, the study found that 2-EH was better additive to diesel than 1-PN.